2023
DOI: 10.3390/ijms241914577
|View full text |Cite
|
Sign up to set email alerts
|

Phloridzin Docosahexaenoate Inhibits Spheroid Formation by Breast Cancer Stem Cells and Exhibits Cytotoxic Effects against Paclitaxel-Resistant Triple Negative Breast Cancer Cells

Wasundara Fernando,
Rikki F. Clark,
H. P. Vasantha Rupasinghe
et al.

Abstract: The eradication of cancer stem cells (CSCs) is vital to successful cancer treatment and overall disease-free survival. CSCs are a sub-population of cells within a tumor that are defined by their capacity for continuous self-renewal and recapitulation of new tumors, demonstrated in vitro through spheroid formation. Flavonoids are a group of phytochemicals with potent anti-oxidant and anti-cancer properties. This paper explores the impact of the flavonoid precursor phloridzin (PZ) linked to the ω-3 fatty acid do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Phlorizin docosahexaenoate, a novel fatty acid ester of plant polyphenols, inhibits the formation of spheroids in breast cancer stem cells and exhibits cytotoxic effects on paclitaxelresistant triple-negative breast cancer cells [80][81][82]. It can be seen that the acylated derivatives of phlorizin have good biological activity in anti-cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Phlorizin docosahexaenoate, a novel fatty acid ester of plant polyphenols, inhibits the formation of spheroids in breast cancer stem cells and exhibits cytotoxic effects on paclitaxelresistant triple-negative breast cancer cells [80][81][82]. It can be seen that the acylated derivatives of phlorizin have good biological activity in anti-cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al synthesised derivatives of apigenin and found one-compound 15e-with strong activity (IC50 of 0.49 versus 44 microM of apigenin) against the growth of human renal carcinoma cells [203]. More recently, Fernando et al reported a fatty acid ester of phloridzin that inhibited spheroid formation by breast cancer cells in vitro [204]. The conjugate could also inhibit the metabolic activity and induce cell death of paclitaxel-resistant variants, while investigation of the effects on stemness markers at low concentrations is warranted [204].…”
Section: Other Natural Compounds and Derivativesmentioning
confidence: 99%
“…More recently, Fernando et al reported a fatty acid ester of phloridzin that inhibited spheroid formation by breast cancer cells in vitro [204]. The conjugate could also inhibit the metabolic activity and induce cell death of paclitaxel-resistant variants, while investigation of the effects on stemness markers at low concentrations is warranted [204]. A synthetic analogue of genistein was also demonstrated to attenuate the expression of FoxM1 and other stemness features of gastric, ovarian, and lung cancer cells [164].…”
Section: Other Natural Compounds and Derivativesmentioning
confidence: 99%